The use of remote sensing and Geographic Information System (GIS) techniques, to interpret savanna ecosystem patterns in the Sabi Sand Game Reserve, Mpumalanga province - Fortescue, Alexander Kenneth John (Rhodes University, Faculty of Science, Department of Geography, 1997)
This thesis explores techniques which ultimately strive to optimize production systems in rangeland areas of southern Africa. By linking spatially significant, satellite derived data to practical measurements of vegetation structure, valuable insight has been derived on processes of ecosystem function, in the Sabi Sand Game Reserve. A broad ecosystem response mechanism has been established from a conventional Normalized Differentiation Vegetation Index (NDVI). By responding to increases in production, which are driven by disturbance, this index has allowed quantitative systems theory in savanna to be tested and refined. Methods of biomass and production estimation which are specifically designed to reduce the cost and time involved with the more conventional method of destructive harvesting have been tested in the savanna at the Sabi Sand Game Reserve. Results from these estimates relate well with data derived through destructive harvesting in structurally similar savanna. Moreover, by relating the above-ground woody production estimates to remere sensing indices, it was possible to demonstrate that the problem of extrapolation, universal to most biomass and production studies can be overcome. Since remote sensing encompasses an array of tools fundamental to rangeland inventory, monitoring and management, valuable spatially significant information pertaining to ecosystem structure and function has been provided for managers in the Sabi Sand Game Reserve.
Keywords: Sabi-Sand Game Reserve (South Africa); Savanna ecology -- South Africa -- Mpumalanga; Geographic information systems; Savanna ecology -- Remote sensing